Supporting software evolution actions with process mining - Calegari, Daniel; Delgado, Andrea (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2023)
There are several forces driving software evolution. One is the business process (BP) misalignment, i.e., when the behavior of the information systems supporting the BPs, or its users, is not aligned with the intended behavior of the BPs identified during the requirement engineering phase. Process Mining (PM) is an essential strategy for BP alignment evaluation. Nevertheless, PM initiatives do not usually focus on connecting BP alignment misfits with concrete software requirements for software evolution. This paper provides initial insights into how PM can support software evolution actions by considering research questions posed during a PM initiative. We exemplify this idea by analyzing administrative procedures within an Electronic Document Management System, providing action guides for its evolution obtained from the PM initiative.